2017
DOI: 10.1534/genetics.117.300270
|View full text |Cite
|
Sign up to set email alerts
|

A Powerful Framework for Integrating eQTL and GWAS Summary Data

Abstract: Two new gene-based association analysis methods, called and for GWAS individual-level and summary data, respectively, were recently proposed to integrate GWAS with eQTL data, alleviating two common problems in GWAS by boosting statistical power and facilitating biological interpretation of GWAS discoveries. Based on a novel reformulation of PrediXcan and TWAS, we propose a more powerful gene-based association test to integrate single set or multiple sets of eQTL data with GWAS individual-level data or summary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 43 publications
(44 reference statements)
1
81
0
Order By: Relevance
“…As discussed in Xu et al. (), in spite of the connections of TWAS with two‐stage least squares and Mendelian randomization (MR), due to the adopted strong assumptions that are likely to be violated in practice, cautions should be taken to avoid extrapolating any discovered GWAS associations to causal effects mediated through gene expression. Hence, we simply regard TWAS as a special case of weighted association testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in Xu et al. (), in spite of the connections of TWAS with two‐stage least squares and Mendelian randomization (MR), due to the adopted strong assumptions that are likely to be violated in practice, cautions should be taken to avoid extrapolating any discovered GWAS associations to causal effects mediated through gene expression. Hence, we simply regard TWAS as a special case of weighted association testing.…”
Section: Discussionmentioning
confidence: 99%
“…Note that, with GWAS individual‐level data, TWAS can be interpreted as testing for association between an imputed gene expression and the GWAS trait; however, with GWAS summary data, WZ may be regarded as an imputed z ‐ score for the gene, but not imputed expression level. It turns out that TWAS is equivalent to the weighted Sum test (Pan, ; Xu et al., ). Because the Sum test implicitly assumes that all variants have an equal effect size and the same effect direction, the Sum test and thus TWAS, as discussed in the previous studies (Pan, ; Pan et al., ; Wu et al., ), may lose statistical power if the true association effects are sparse (i.e., with many 0s) or the effect directions are different.…”
Section: Methodsmentioning
confidence: 99%
“…Xu et al (2017) showed that, more generally, any more powerful tests, such as an adaptive aSPU test, can be applied. The aSPU test is based on choosing one of the SPU tests, SPU( γ ) with positive integers γ ≥ 1 in a candidate set, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…We consider an arbitrary gene and a set of k SNPs in some region around the gene: X=(X1,,Xk). We have the corresponding score vector: U=(U1,,Uk) with Uj=Xjtrue′false(Ytrueμˆ0false), where μˆ0 is the estimated mean of Y under the null hypothesis: H0 :β=false(β1,,βkfalse)=0. Given the weights trueWˆ, we denote the weighted score statistics as: U*=WˆU=(truewˆ1U1,,truewˆkUk). Thus, we can construct the following TWAS test statistic, where we aggregate weighted score statistics across a gene: TTWAS=j=1kUj*. We now consider the extension of TWAS to other SPU tests (Xu et al, ). Xu et al make the observation that TWAS is equivalent to a weighted Sum test of multiple SNPs in a generalized linear model (2).…”
Section: Methodsmentioning
confidence: 99%
“…The TWAS and PrediXcan test statistics can be thought of as weighted sum tests. This framework can be extended to other sums of powered score (SPU) tests (Su et al, ; Xu, Wu, Wei, & Pan, ), and to other mediating phenotypes in addition to gene expression (Xu, Wu, & Pan, ). It has been convincingly shown that PrediXcan and TWAS increase the power of GWAS analyses for certain complex traits, and help inform the biological mechanism by which SNPs influence the expression of complex traits.…”
Section: Introductionmentioning
confidence: 99%